Psychoeducation through home care strengthens family coping in elderly stroke rehabilitation - Aan Nurhasanah; Yuli Mulyanti; Sri Djuwitaningsih; Rosidawati Rositawati; Eros Siti Suryati (Healthcare in Low-resource Settings)
Post-stroke patients undergoing rehabilitation require family assistance to perform their daily activities. The family’s responsibilities as caregivers can create psychological, social, physical, and financial burdens, highlighting the need for coping strategies that enhance the ability of families and caregivers to alleviate these burdens without jeopardizing their health. Family caregivers are important in providing psychoeducation to post-stroke rehabilitation patients through home care. The aim of this study was to evaluate the effectiveness of home care in improving family coping strategies for elderly individuals undergoing stroke rehabilitation. A quasi-experimental design was implemented with a pre-post-test and control on 64 families, selected by purposive sampling. Data were collected using a closed questionnaire and analyzed through t-tests (univariate and bivariate) and multivariate analysis of covariance (MANCOVA). The research results showed significant differences in knowledge before and after being given psychoeducation through home care (p=0.001), with a difference in average value of 0.9183, and family coping scores with a p-value of 0.035, with a difference in average value of 1.100. Providing psychoeducation through home care can significantly enhance family coping mechanisms when caring for elderly patients undergoing stroke rehabilitation. As an independent nursing intervention, psychoeducation, delivered in the context of appropriate home care, plays a crucial role not only in empowering families but also in optimizing the environment for recovery.